Scope of the reductive aldol reaction: application to aromatic carbocycles and heterocycles. - Donohoe, T; House, D; Ace, K (2003)
The reductive aldol reaction of electron deficient aromatic compounds has been investigated and found to be a viable method for carbon-carbon bond formation. Reductions under ammonia and ammonia-free conditions were both capable of facilitating the aldol reaction although the latter showed more scope for reaction with enolisable aldehydes. Moreover, reduction under ammonia-free conditions allowed the addition of Lewis acids which improved stereoselectivity to favour the anti stereoisomer. Production of the syn diastereoisomer was possible through either one of two different protocols performed after partial reduction was complete. While the main emphasis of this paper concerns the reductive aldol reaction of electron deficient pyrroles, it was also shown that both benzenoid and furan aromatic compounds were amenable to such reducing conditions.